2019
DOI: 10.1371/journal.pone.0216989
|View full text |Cite
|
Sign up to set email alerts
|

Detection of mammagloblin by RT-PCR as a biomarker for lymph node metastasis in breast cancer patients: A systematic review and meta-analysis

Abstract: Background This meta-analysis presents evidence regarding the diagnostic accuracy of mammaglobin detected using the RT-PCR technique, related to the presence of sentinel node metastasis in breast cancer patients. Methods The following databases were consulted: Cochrane, Lilacs, Scielo, Hinary, PubMed, Elsevier, Embase, ProQuest, the Universidad del Rosario´s Centro de Recursos Para el Aprendizaje y la Investigación (CRAI-UR) [Resource Center for Learning and Research], … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…It is noteworthy that RT-PCR found broad applications in diagnostics and treatment monitoring in oncology [ 53 ]. It has been used in research of prognostic and predictive tumor biomarkers, e.g., in breast cancer [ 54 ], melanoma [ 55 , 56 ], or hepatocellular carcinoma [ 57 , 58 ], as well as for other purposes, such as micrometastasis determination [ 59 ] or detection of circulating tumor cells [ 60 , 61 ]. In this method complementary DNA (cDNA) is generated from RNA template in reverse transcription and specific DNA targets are amplified using polymerase chain reaction (PCR), employing large set of primer pairs.…”
Section: Transcriptome’s Components and Methods Of Its Analysismentioning
confidence: 99%
“…It is noteworthy that RT-PCR found broad applications in diagnostics and treatment monitoring in oncology [ 53 ]. It has been used in research of prognostic and predictive tumor biomarkers, e.g., in breast cancer [ 54 ], melanoma [ 55 , 56 ], or hepatocellular carcinoma [ 57 , 58 ], as well as for other purposes, such as micrometastasis determination [ 59 ] or detection of circulating tumor cells [ 60 , 61 ]. In this method complementary DNA (cDNA) is generated from RNA template in reverse transcription and specific DNA targets are amplified using polymerase chain reaction (PCR), employing large set of primer pairs.…”
Section: Transcriptome’s Components and Methods Of Its Analysismentioning
confidence: 99%
“…The Q-RT-PCR technique is a rapid, cost-effective, and high-specificity assay for the assessment of gene expression [ 12 ]. Q-RT-PCR technique has significant potential in biomarker detection relating to mammaglobin (MGB) and metastasis of the lymph nodes [ 17 ]. For example, it has been recently shown that RT-PCR had a considerable diagnostic prediction for detecting mammaglobin biomarkers for lymph node metastasis in breast cancer patients [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-study systematically evaluated the clinical efficacy and cost-effectiveness of one-step nucleic acid amplification (OSNA) and Metasin in the intraoperative analysis of SLN metastasis in breast cancer patients. And proposed that the OSNA test only analyzes cytokeratin 19 (CK19) gene expression, while the Metasin analysis analyzes CK19 and mammaglobin gene expression ( 6 ). In this study, we focused more on intraoperative analysis of the plausibility of the expression of two markers in sentinel lymph nodes as biomarkers for the presence of metastases.…”
Section: Introductionmentioning
confidence: 99%